Designing Responsible Assessment in SSH: A Checklist - Delmazo, Carol; Mystakopoulos, Fotis (Zenodo (CERN European Organization for Nuclear Research), 2025)
Note: Version 2 includes a correction in the DOIs. Designing Responsible Assessment in SSH: A checklist Supplementary Information Authors & Contact details: Carol Delmazo (https://orcid.org/0000-0002-8284-9117) – carol.delmazo@operas-eu.org Fotis Mystakopoulos (https://orcid.org/0000-0002-9354-3754) – fotis.mystakopoulos@operas-eu.org Affiliation: OPERAS Research Infrastructure Project Funding: The GraspOS project has received funding from the European Union’s Horizon Europe framework programme under grant agreement No. 101095129. About This Document This supplementary checklist accompanies the document, Guidance and recommendations for research assessment in SSH: Lessons learned in the GraspOS project (Delmazo, C., & Mystakopoulos, F. (2025). Guidance and recommendations for research assessment in SSH: Lessons learned in the GraspOS project. Zenodo. https://doi.org/10.5281/zenodo.17951789). It provides a quick summary of the purpose of the checklist, and how to use it for implementing responsible research assessment in Social Sciences and Humanities (SSH) contexts. Purpose of the Checklist The checklist is designed to help institutions, funders, and evaluation bodies design and implement research assessment processes that respect SSH specificities. It draws on the established SCOPE framework, and as it was implemented in the GraspOS Project, and aligns with the principles of the Coalition for Advancing Research Assessment (CoARA). The checklist addresses common pitfalls in research assessment, such as over-reliance on bibliometric indicators (e.g., h-index, Journal Impact Factor), the exclusion of diverse research outputs, and structural biases that disadvantage certain career stages or disciplinary traditions, but with an extra focus on what those elements mean for SSH. Intended Audience This checklist is intended for: • Research institutions developing or reforming internal assessment policies • Funding agencies designing evaluation criteria for SSH research • Evaluation committees seeking to implement fair and context-sensitive processes • Policy makers working on research assessment reform at national or international levels • Individual researchers advocating for responsible assessment practices How to Use This Checklist The checklist builds on the SCOPE Framework, adding an initial design phase to create six key stages of assessment design. It is intended to be used iteratively rather than as a one-time exercise.